2007
DOI: 10.1097/01.nmd.0000243826.40732.45
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and 12-Month Prevalence of DSM-IV Psychiatric Disorders Among Korean Adults

Abstract: The objective was to estimate the prevalence and correlates of psychiatric disorders in a nationwide sample of Korean adults. Face-to-face interviews were conducted with the Korean version of Composite International Diagnostic Interview 2.1/DSM-IV (N = 6275, response rate 79.8%). The lifetime and 12-month prevalences for all types of DSM-IV disorders were 33.5% and 20.6%, respectively. Those of specific disorders were as follows: 17.2% and 7.1% for alcohol use disorder, 11.2% and 7.4% for nicotine use disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
160
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(176 citation statements)
references
References 22 publications
13
160
1
1
Order By: Relevance
“…[98] More recent estimates using the CIDI and DSM-IV criteria show greater cross-national variability. No cases were reported in metropolitan China, [12] and rates of 12-month OCD among adults are 0.1% (SE=0.1) in Nigeria, [43] 0.5% (SE=0.1) in The Netherlands, [99] 0.6% in Germany, [63] 0.6% (SE=0.1) in South Korea, [45] 0.7% (SE=0.1) in Australia, [44] 1% (SE=0.3) in the United States, [60] and 3% in Turkey. [100] Median prevalence in 16 European countries is 0.7%, with an interquartile range of 0.5-1.1%.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…[98] More recent estimates using the CIDI and DSM-IV criteria show greater cross-national variability. No cases were reported in metropolitan China, [12] and rates of 12-month OCD among adults are 0.1% (SE=0.1) in Nigeria, [43] 0.5% (SE=0.1) in The Netherlands, [99] 0.6% in Germany, [63] 0.6% (SE=0.1) in South Korea, [45] 0.7% (SE=0.1) in Australia, [44] 1% (SE=0.3) in the United States, [60] and 3% in Turkey. [100] Median prevalence in 16 European countries is 0.7%, with an interquartile range of 0.5-1.1%.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
“…Among adults, for example, 12-month rates of DSM-IV-defined PD based on the CIDI range from 0.1% (SE=0.0) in Nigeria [43] to 1.1% (SE=0.1) in Australia. [44] Rates are 0.2% (SE=0.1) in South Korea, [45] 0.2% (SE=0.1) in metropolitan China, [12] 0.5% (95% CI=0.0-1.1) in Japan, [46] 0.6% (SE=0.1) in Mexico, [47] and 0.8% (SE=0.2) in South Africa. [48] A comprehensive assessment of 27 studies in Europe revealed a 12-month median prevalence of 1.8%, with an inter-quartile range of 0.7-2.2%, more similar to US surveys.…”
Section: Panic Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…21 A recent study in metropolitan China using WHO Composite International Diagnostic Interview found that the lifetime prevalence of DSM-IV bipolar I and II disorders was only 0.1%, 22 while a similar study in Korea showed that the lifetime prevalence was 0.2%. 23 Kawakami et al found that the lifetime prevalence of DSM-III-R bipolar disorder in Japan was 0.1%. 24 A local study in the mid-1980s showed that the lifetime rate for bipolar disorder using the DSM-III criteria was 0.15%.…”
mentioning
confidence: 99%
“…Epidemiological studies suggest that OCD is observed more frequently in females compared to males [16][17][18][19][20]. Moreover, the mean age of onset of OCD in women is in the reproductive age group [20].…”
Section: Brief Overview Of Various Mental Disorders During Pregnancy mentioning
confidence: 99%